Perkembangan kinerja fundamental dan harga saham emiten telekomunikasi di bei selama pandemi covid-19 hingga perilisan starlink: analisis deskriptif - Erbean, Sherif Prast (Maliki Interdisciplinary Journal, 2025)
This study aims to describe the development of fundamental ratios and stock price movements in telecommunications sub-sector issuers on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. This period was chosen because it covers two important events: the COVID-19 pandemic and the entry of Starlink satellite internet services into the Indonesian market. This study uses a descriptive approach with secondary data in the form of Price to Earnings Ratio (PER), Price to Book Value (PBV), and Earnings per Share (EPS) ratios from three large companies: PT Telkom Indonesia (TLKM), PT Indosat Tbk (ISAT), and PT XL Axiata Tbk (EXCL). The results of the analysis show that ISAT experienced the most significant growth in fundamental performance and stock prices after the merger with Hutchison Tri. Meanwhile, TLKM showed strong stability and EXCL recorded moderate development. The presence of Starlink in 2023 has not had a major direct impact on the three companies, but is an early signal of potential market disruption. This study provides an overview for investors and industry players regarding the response of telecommunications issuers to external dynamics that affect fundamentals and stock values